A caution against customized AI in healthcare - Kristin M. Kostick-Quenet (npj Digital Medicine)
Abstract This article critiques the shift towards personalized AI in healthcare and other high-stakes domains, cautioning that without careful deliberation, customized AI systems can compromise the diversity and reach of human knowledge by restricting exposure to critical information that may conflict with users’ preferences and biases. Customized AI should be applied with caution and intention where access to a wide and diverse range of perspectives is essential for impartial, informed decision making.